Lime-Phosphorus Fertilizer Efficiently Reduces the Cd Content of Rice: Physicochemical Property and Biological Community Structure in Cd-Polluted Paddy Soil - Kuang, Xiaolin; Si, Kangying; Song, Huijuan; Peng, Liang; Chen, Anwei (Frontiers in Microbiology, 2021)
Due to the biomagnifying effect in the food chains, heavy metals will cause serious harm to the food produced in paddy soil, and then threaten human health. The remediation of soil heavy metals by the addition of amendments is a common method. However, the combination of the two amendments has been less studied and its effect is unknown. In this study, We investigated the effects of different concentrations of a lime and calcium-magnesium phosphate amendments metal availability and paddy soil bacteria biodiversity. The experiment proves that the addition of 0.5‰ and 1.0‰ amendment can effectively reduce cadmium (Cd) availability and the cadmium content in rice to below 0.2 mg/kg, meeting the national food safety level. The results demonstrate that increasing pH and phosphorous (P) in soil were two important factors decreasing available cadmium. Furthermore, biodiversity analysis of the treated soil showed that the amendment increased biodiversity. Proteobacteria and Chloroflex were the most abundant bacteria at the phylum level, followed by Acidobacterium and Nitrospirae. The abundance of Bacterodietes-vadinHA17, Syntrophaceae, and Thiobacillusincreased as phosphorous increased. Cadmium passivation might induce those species.